An integrated approach of bioleaching-enhanced electrokinetic remediation of heavy metals from municipal waste incineration fly ash using Acidithiobacillus spp - Narenkumar, Jayaraman; Sathishkumar, Kuppusamy; Das, Bhaskar; Rajasekar, Aruliah; Rajakrishnan, R.; Rajamohan, Rajaram; Malik, Tabarak (Frontiers in Environmental Science, 2023)
Municipal Solid Waste (MSW) incineration fly ash is a harmful residue formed during the incineration process. It contains high concentrations of hazardous heavy metals like lead, zinc, aluminum, and iron. In this research, the combination of bioleaching integrated with an electrokinetics approach for heavy metal remediation from MSW incineration fly ash using Acidithiobacillus ferrooxidans and Acidithiobacillus thiooxidans bacteria. The results of the physicochemical properties of fly ash showed 26.1 μm of particle size with the presence of heavy metals. A.Ferrooxidans and A.Thiooxidans produced sulphuric acid (0.0289M and 0.0352M) during the proliferation, this acid enhances the bioleaching of heavy metal from fly ash. The results of an integrated approach showed 85%, 47%, 92%, 85%, 46%, 67% 11% and 55% of K, Na, Ca, Mg, Al, Zn, Pb and Mg respectively removal of heavy metal in the presence of A.Ferrooxidans. Overall these results evidenced that heavy metals were completely removed from the fly ash by an integrated approach. Hence, this integrated approach can be used as an effective heavy metal removal method to treat fly ash in the MSW.